Living labeled: how students make meaning of their label of autism - Casola, Shona (My University, 2015)
The purpose of this study is to examine how high school students labeled with autism make meaning of their label and how, for them, the label functions in their day-to-day lives. Being diagnosed with autism can have many implications for an individual and his or her family and how a label is understood is very much connected to the impact that it has. A label can be instrumental in accessing resources and supports that enable a person to thrive, but it can also conjure stereotypes which may categorize a person or limit them in particular ways. Using critical theory and phenomenological analysis, short semi-structured interviews were conducted with high school aged participants prior to their attending a full day workshop. The workshop included half-day art creation and a half-day focus group which sought to understand participants’ experiences through their descriptions of their art and through collaborative discussion about their experience living labeled. The findings suggest that while their experiences are as diverse as the individuals who have them, there are similarities in how the label functions which may be more universal. Participants in this study discussed how the label of autism assigns positive or (more often) negative value to a person; how their label linked them with certain resources (and not others), and how they experienced and understood these resources; and the way labels can both protect and confine a person. Consideration of how high school students understand of their label of autism can prompt us all to think more critically about how labels, and the meanings we assign to them, affect and shape experience for those who live labeled.
Keywords: Autism, Labeling, Accommodation, Expectation, Value/Undervalue, High school students, critical disability studies